2021
DOI: 10.1101/2021.03.10.434722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and dynamics of the SARS-CoV-2 envelope protein monomer

Abstract: Coronaviruses, especially SARS-CoV-2, present an ongoing threat for human wellbeing. Consequently, elucidation of molecular determinants of their function and interaction with host is an important task. Whereas some of the coronaviral proteins are extensively characterized, others remain understudied. Here, we use molecular dynamics simulations to analyze the structure and dynamics of the SARS-CoV-2 envelope protein (E protein, a viroporin) in the monomeric form. The protein consists of three parts: hydrophobi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 107 publications
5
13
0
Order By: Relevance
“…Even this model was stable only on the hundreds-of-nanoseconds time scale, and was not evidently permeable to Ca 2+ . Although several articles and preprints in the past year (Borkotoky & Banerjee, 2020; Cao et al, 2020; Gadhave et al, 2020; Gentile et al, 2020; Gupta et al, 2020; Kuzmin et al, 2021; Yu et al, 2021) have reported simulations of this structure, a review of their results shows similar limitations, with abbreviated timescales (Borkotoky & Banerjee, 2020; Gentile et al, 2020; Gupta et al, 2020), reliance on secondary-structure restraints (Cao et al, 2020), elevated RMSDs (Borkotoky & Banerjee, 2020; Cao et al, 2020), and/or dewetting in the absence of electric fields (Cao et al, 2020). Instability of the open structure may reflect underdetermination of the starting protein or membrane models, unresolved interactions with the C-terminal or other domains, or other factors yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even this model was stable only on the hundreds-of-nanoseconds time scale, and was not evidently permeable to Ca 2+ . Although several articles and preprints in the past year (Borkotoky & Banerjee, 2020; Cao et al, 2020; Gadhave et al, 2020; Gentile et al, 2020; Gupta et al, 2020; Kuzmin et al, 2021; Yu et al, 2021) have reported simulations of this structure, a review of their results shows similar limitations, with abbreviated timescales (Borkotoky & Banerjee, 2020; Gentile et al, 2020; Gupta et al, 2020), reliance on secondary-structure restraints (Cao et al, 2020), elevated RMSDs (Borkotoky & Banerjee, 2020; Cao et al, 2020), and/or dewetting in the absence of electric fields (Cao et al, 2020). Instability of the open structure may reflect underdetermination of the starting protein or membrane models, unresolved interactions with the C-terminal or other domains, or other factors yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Even this model was stable only on the hundreds-of-nanoseconds time scale, and was not evidently permeable to Ca 2+ . Although several articles and preprints in the past year 74,[79][80][81][82][83][84] have reported simulations of this structure, a review of their results shows similar limitations, with abbreviated timescales, [80][81][82] reliance on secondary-structure restraints, 74 elevated RMSDs, 74,80 and/or dewetting in the absence of electric fields. 74 Instability of the open structure may reflect underdetermination of the starting protein or membrane models, unresolved interactions with the C-terminal or other domains, or other factors yet to be identified.…”
Section: Since the [Ca 2+mentioning
confidence: 93%
“…The ERGIC membrane may consist of 55% phosphatidylcholine (PC), 25% phosphatidylethanolamine (PE), 10% phosphatidylinositol (PI), 5% phosphatidylserine (PS), and 5% sphingomyelin (SM) and, its Chol (Cholesterol)/PS molar ratio may be approximately 3.5. 16 , 17 , 18 , 19 , 20 This membrane is made of lipid bilayers with a monolayer separation of 3.6 nm (thickness d = 7.2 nm), after assembly of the virus, has a nearly spherical shape with a diameter of approximately 90 nm (radius r = 45 nm) and referred to as the viral envelope. 17 , 21 Within the viral envelope, approximately 30‐kb long (+) ssRNA and viral ribonucleoprotein (vRNP) complexes are located.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that the protein-lipid interplay around the E-channel is very complex. An additional homology model 14 has been proposed since the start of our study, simulations of an E monomer to characterize the orientation of the helices in the sequence, 57 an experimental structure for the TMs (7K3G). 11 It remains to be determined if the preferred E channel conformation resembles the Korkin model, or if a conformation like the one proposed by the Feig model is biologically relevant at a given stage of the viral life cycle.…”
Section: Given the Degree And Extent Of Deformation Induced By The Open Conformation It Is Possible Thismentioning
confidence: 99%